Effect of zero-valent iron combined with carbon-based materials on the mitigation of ammonia inhibition during anaerobic digestion. (September 2020) - Liu, Jibao; Zheng, Jiaxi; Niu, Yutong; Zuo, Zhuang; Zhang, Junya; Wei, Yuansong
Graphical abstract: Highlights: 4 g/L of ZVI mitigated inhibition of AD under ammonia stress of 5 g/L. ZVI activated Methanosarcina thus reduced methane production lag phase by 45%. Its hybrid with carbon-based material further shortened lag phase over 63%. Hydrogenotrophic methanogenesis was activated mostly through enhanced DIET. Abstract: Ammonia inhibition is a prominent problem for anaerobic digestion (AD) of nitrogen-rich organic wastes. This study evaluated the effect of zero valent iron (ZVI) and its hybrid with activated carbon (AC), graphite and Fe-C material on the mitigation of ammonia inhibition under ammonia concentration over 5 g/L, according to the batch mode experiments. Results showed that ZVI (4 g/L) and its hybrid with carbon-based material preserving methane production from ammonia inhibition, with kinetics of shortening lag phase from 4.77 d to 2.62 d or even below 2 d with carbon-based material. ZVI preserved methane production with the enrichment of Methanosarcina (the relative abundance was over 80%), which was mostly derived from the activating hydrogenotrophic methanogenesis through the enhanced DIET but not the changes of ORP and FAN.